Characterization of circulating molecules and activities in plasma of patients after allogeneic and autologous intraoral bone grafting procedures: a prospective randomized controlled clinical trial in humans - Önder Solakoglu; Bettina Steinbach; Werner Götz; Guido Heydecke; Heidi Schwarzenbach (BMC, 2022)
Abstract Background The objective was to assess whether intraoral bone augmentation procedures have an impact on the patient's plasma levels of circulating nucleic acids, exosomes, miRNA levels and caspase activities. The null hypothesis was tested, that no significant differences between the two groups will be found. Methods In this prospective randomized controlled clinical trial 35 systemically healthy non-smoking participants were randomly allocated using sealed envelopes by a blinded clinician not involved in the clinical setting. Plasma samples were collected preoperatively and 3 times postoperatively (immediately, 5 weeks and 4 months postoperatively). The test group consisted of twenty-five patients who received allogeneic bone grafting material and the control group of ten patients who received autologous bone grafts. Levels of cell-free DNA (cfDNA) and microRNAs (miR-21, miR-27a, miR-218) were quantified by real-time PCR, caspase activities and exosome concentrations were determined by ELISA. Results Statistical evaluation reveled a significantly higher exosome level before surgery (p = 0.013) and the first postsurgical sample (p = 0.017) in the control group compared to the test group. The levels of miR-27a and miR-218 significantly differed between the plasma samples before surgery and after surgery in both groups. The levels of miR-21 only significantly differed between the pre- and postsurgical plasma samples in the test group, but not in the control group. All patients completed the study, no adverse events were recorded. Conclusions Our data show the diagnostic potential of the plasma levels of miR-27a, miR-218 and miR-21 in detecting changes in bone metabolism after alveolar bone augmentation. Our very promising results indicate that there might be a high diagnostic potential in evaluating the plasma levels of the before mentioned miRNAs in order to detect bone resorption activities before they become clinically relevant. Trial registration Ethical commission of the Ärztekammer Hamburg, Germany (PV5211) on 11/03/2016 as well as by the German Registry of Clinical Studies (DRKS 00,013,010) on 30/07/2018 ( http://apps.who.int/trialsearch/ ).